Effect of nanoscale precipitation on strengthening of ferritic ODS Fe-Cr-Al alloy. (1st October 2013) - Capdevila, C.; Chao, J.; Jimenez, J. A.; Miller, M. K.
<x xml:space="preserve">Abstract</x> The kinetics of Fe rich  and Cr rich ′ phase separation during aging of Fe-Cr-Al oxide dispersion strengthened alloys have been analysed with a combination of atom probe tomography and thermoelectric power measurements. The slight lattice parameter decrease measured by X-ray diffraction after thermal aging was associated with a lattice misfit between the emerging  and ′ domains. The elastic strain associated with this misfit and the different elastic moduli for the  and ′ phases would produce an increase in internal stresses that would retard the motion of dislocations and thus would be the main cause for the strengthening.